Effects of violence on executive function: a neuropsychological and predictive analysis in victims of the armed conflict in Colombia - Camargo, Loida; Patricia Manjarrés, Aida; Martínez-Gonzalez, Marina B. (Frontiers in Human Neuroscience, 2026)
IntroductionExposure to violence has been associated with alterations in how the brain organizes thought, regulates emotions, and guides behavior. In Colombia, decades of armed conflict have generated heterogeneous patterns of cognitive vulnerability, yet evidence on executive and emotional functioning in adult victims remains limited.MethodsThis cross-sectional study compared executive and emotional functioning between victims and non-victims of the Colombian armed conflict. A total of 300 middle-aged adults from the Department of Bolívar were assessed using a neuropsychological battery (MMSE, Tower of Hanoi, Wisconsin Card Sorting Test, Stroop Test, and Frontal Assessment Battery) and emotional screening instruments (GAD-7 and PHQ-2). Executive function was modeled as a latent construct using confirmatory factor analysis and Multiple Indicators Multiple Causes (MIMIC) models adjusted for sociodemographic covariates. Random Forest was implemented as a complementary, assumption-free analytic strategy.ResultsVictims showed significantly poorer performance in planning, cognitive flexibility, and inhibitory control (β = –0.178; p = 0.024). Educational attainment emerged as the strongest predictor of executive functioning (β = –0.249; p < 0.001). The factorial model showed modest fit (CFI = 0.76), reflecting ecological and educational heterogeneity. Machine learning analyses converged with latent-variable results, identifying exposure to violence and structural inequalities as the strongest predictors of executive variability, whereas emotional factors played a marginal role.DiscussionThe findings delineate a cognitive profile associated with conflict-related victimization, characterized by vulnerabilities in executive control processes. These results underscore the need for clinical and public policy interventions that integrate neuroscientific approaches to strengthen planning and decision-making capacities in populations affected by armed conflict.